What is violence? An analysis about the use of the term in behavior-analytic literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The goal of this work was to analyze the use of the term “violence” in behavior analysis literature. Specifically, we aimed to locate and describe the research categories about violence, the thematic domains of violence studies, and the main behavioral categories associated with violence. We argued there is not a consensual definition of violence in behavior-analytic literature. The use of the term seems to be associated with (a) specific topographies of response or to its harmful effects (not function), (b) aggression, (c) coercion, (d) the escape function of violent behavior, (e) its role as aversive condition that leads to escape or avoidance pattern, and, especially in cultural analyses, (f) with macrosocial conditions that engender a variety of cultural practices instead of the behavior of a particular agent. We ended this paper with some reflections on the consequences of adopting those different characteristics associated with violence.
Keywords: behavior analysis; violence; coercion; aggression; forms of violence; conceptual research